Pandemic and racism: socio-racial inequalities in the context of the pandemic - Bittencourt, Júlia Barcelos; Silva, Mossicleia Mendes (Argumentum, 2023)
This analysis focuses on the deepening of socio-racial inequalities in the context of the Covid-19 Pandemic, given that this has highlighted the contradictions of the system of capital. This article aims to understand how the State prioritises the protection of the production and accumulation of capital to the detriment of the protection of workers lives, and reflects on the deepening of socio-racial inequalities. It is based on an analysis of the historical determinations of racism and the overexploitation of the workforce as structuring pillars of Brazilian society. It concludes that the social and economic impacts of the Covid-19 Pandemic fell mainly on the black and poor population; the population historically already in more precarious living and working conditions.